2008
DOI: 10.1183/09031936.00171707
|View full text |Cite
|
Sign up to set email alerts
|

Physical training does not increase allergic inflammation in asthmatic children

Abstract: The effects of a 3-month physical training programme on airway inflammation and clinical outcomes were studied in school-aged children with asthma.Subjects with persistent allergic asthma (aged 12.7¡3.4 yrs; n534) were randomly allocated into training and control groups. Exercise consisted of twice-weekly 50-min sessions for 12 weeks. Inflammation was assessed by levels of exhaled nitric oxide, blood eosinophils, eosinophil cationic protein, C-reactive protein, and total and mite-specific immunoglobulin (Ig)E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
4
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(161 citation statements)
references
References 30 publications
(32 reference statements)
7
138
4
9
Order By: Relevance
“…However, regular exercise has been found not to influence resting lung function 29 and bronchial responsiveness to methacholine. 30 This suggests that greater bronchial responsiveness leads to decreased activity. It has been argued that if asthmatic subjects are restricting their physical activity because of asthma symptoms, this indicates that the asthma is not being well controlled and steps should be taken to improve the management of the asthma.…”
Section: Discussionmentioning
confidence: 99%
“…However, regular exercise has been found not to influence resting lung function 29 and bronchial responsiveness to methacholine. 30 This suggests that greater bronchial responsiveness leads to decreased activity. It has been argued that if asthmatic subjects are restricting their physical activity because of asthma symptoms, this indicates that the asthma is not being well controlled and steps should be taken to improve the management of the asthma.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, physical activity directly decreases the levels of inflammatory markers, CRP, TNF and in most studies also IL-6, increases Treg cell numbers and enhances the production of IL-10 and TGFβ (94,95), indicating clear anti-inflammatory properties. In asthmatic school children, physical training for 3 months decreased both total and allergen (mite)-specific IgE levels (96). However, physical activity still remains a largely neglected aspect of prevention and intervention of non-communicable diseases (92).…”
Section: Sedentary Lifestylementioning
confidence: 99%
“…FANELLI et al [20] also reported improved quality of life and asthma control in their actively training group compared with a nontraining group. MOREIRA et al [21] conducted a 3-month training programme in adolescents (mean age 13.4 yrs) and found no changes in asthma control; however, they reported a reduction in total and house dust mite-specific immunoglobulin E in their training group.…”
Section: Participation In Physical Activity and Sports And Training Omentioning
confidence: 97%